Interviewer with Tom Dunigan, Director of Institutional Studies at Cal Poly, November 25, 1967 (1967)
[00:00:02] Interviewer introduces Tom Dunigan, Director of Institutional Studies at Cal Poly [00:00:30] Dunigan talks about the number of students at Cal Poly and the most popular majors [00:00:54] Dunigan lists majors by number of students enrolled [00:01:52] Dunigan discusses the number of women students at Cal Poly and which majors they study [00:03:14] Dunigan talks about the number of full-time students vs part-time students [00:03:55] Dunigan discusses where students come from: in state, other states, and international students from 60 other countries [00:05:13] Interviewer wraps up interview